2005
DOI: 10.1162/0898929052880101
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical Gender and Number Agreement in Spanish: An ERP Comparison

Abstract: Abstract& The role of grammatical gender and number representations in syntactic processes during reading in Spanish was studied using the event-related potentials (ERPs) technique. The electroencephalogram was recorded with a dense array of 128 electrodes while Spanish speakers read word pairs (Experiment 1) or sentences (Experiment 2) in which gender or number agreement relationships were manipulated. Disagreement in word pairs formed by a noun and an adjective (e.g., faro-alto [lighthouse-high]) produced an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

57
328
6
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 336 publications
(396 citation statements)
references
References 35 publications
57
328
6
5
Order By: Relevance
“…Critically, under any neurocognitive account of sentence comprehension (Bornkessel-Schlesewsky and Schlesewsky, 2009a;Friederici, 2002;Hagoort, 2005), this outright syntactic violation should have evoked a P600 effect, which is the ERP effect most commonly associated with syntactically problematic or dispreferred linguistic expressions Van Berkum et al, 2007;Kutas et al, 2006). Moreover, a multitude of electrophysiological studies have reported P600 effects for related gender mismatch violations across different languages (Barber and Carreiras, 2005;Molinaro et al, 2011;Wicha et al, 2004;Van Berkum et al, 2007;Xiang et al, 2009). The fact that the main manipulation in the current study elicited a sustained negativity rather than a P600 effect suggests that the processing consequences of incorrectly gender-marked ellipsis can be qualitatively different from the repair or reanalysis processes as assumed to be indexed by P600 modulations, and perhaps that participants did not treat failure to retrieve an antecedent as a consequence of the gender agreement violation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critically, under any neurocognitive account of sentence comprehension (Bornkessel-Schlesewsky and Schlesewsky, 2009a;Friederici, 2002;Hagoort, 2005), this outright syntactic violation should have evoked a P600 effect, which is the ERP effect most commonly associated with syntactically problematic or dispreferred linguistic expressions Van Berkum et al, 2007;Kutas et al, 2006). Moreover, a multitude of electrophysiological studies have reported P600 effects for related gender mismatch violations across different languages (Barber and Carreiras, 2005;Molinaro et al, 2011;Wicha et al, 2004;Van Berkum et al, 2007;Xiang et al, 2009). The fact that the main manipulation in the current study elicited a sustained negativity rather than a P600 effect suggests that the processing consequences of incorrectly gender-marked ellipsis can be qualitatively different from the repair or reanalysis processes as assumed to be indexed by P600 modulations, and perhaps that participants did not treat failure to retrieve an antecedent as a consequence of the gender agreement violation.…”
Section: Discussionmentioning
confidence: 99%
“…P600 effects are not only reliably elicited by outright syntactic violations (e.g., determiner-noun gender agreement violation; Barber and Carreiras, 2005;Wicha et al, 2004; or subject-verb person agreement violations; Mancini et al, 2011;Molinaro et al, 2011) but also by denial of syntactic preference or expectation, i.e., by constructions that are well-formed but whose syntactic properties do not fit the analysis currently being pursued or that was previously expected (e.g., Carreiras et al, 2004;Van Berkum, 2009). Given that the gender of the determiner (-o/-a) was grammatically correct or incorrect given that of the antecedent (camiseta), grammatically incorrect determiners in our study may thus initially be perceived as a morphosyntactic "dead end", triggering re-analysis (Gouvea et al, 2010;Kaan and Swaab, 2003;Osterhout and Holcomb, 1992).…”
Section: Predictions For Event-related Brain Potentialsmentioning
confidence: 90%
“…The P600 has been argued to reflect syntactic integration (e.g., Kaan, Harris, Gibson, and Holcomb, 2000), reanalysis Examining Morphological Variability in L2 Learners 12 (e.g., Osterhout and Holcomb, 1992) and repair (e.g., Barber and Carreiras, 2005;see Molinaro, Barber, and Carreiras, 2011 for a review). Importantly, although the P600 is not exclusively linked to morphosyntactic processing (i.e., it has been reported for certain types of semantic violations; see Bornkessel-Schlesewsky & Schlesewsky, 2008;Kim & Osterhout, 2005), it is consistently found for morphosyntactic errors in native speakers.…”
Section: The Present Studymentioning
confidence: 99%
“…Since the P600 showed a right-hemisphere bias in both populations, it is possible that the dipole generating the P600 was oriented in such a way that its positive and negative ends were detected by right posterior and left anterior electrodes, respectively (e.g., Barber and Carreiras, 2005). for properties that are unique to the L2, although these appear to be harder. Along these lines, our results also suggest that difficulty with the online processing of gender agreement (property that is unique to the L2) is more tied to lexical (i.e., assignment), than syntactic (i.e., agreement) aspects.…”
mentioning
confidence: 99%
“…At present, experimental evidence concerning the representation of abstract morphosyntactic features is sparse and somewhat inconclusive. The event-related potentials studies exploring neuronal responses after agreement violations reported two main correlates of agreement violations, left anterior negativities (LAN) and a late positivity wave (P600) (Münte et al, 1998;Gunter et al, 2000;Wassenaar et al, 2004;Barber and Carreiras, 2005;Morris and Holcomb, 2005;Nevins et al, 2007;Silva-Pereyra and Carreiras, 2007;Leinonen et al, 2008). Instead of the LAN effect, some studies observed other negativities centered on the parietal sites, labeled N400, after gender violations Carreiras, 2003, 2005, at the noun phrase level, Wicha et al, 2004, at the sentence level).…”
Section: Introductionmentioning
confidence: 99%